Feasibility Study of In-Situ Bioremediation of Atrazine by Pseudomonas SP. ADP (PADP) in a Laboratory Scale Model Aquifer - Shrestha, Binita K.; Shakya, Pawan Raj; Soares, M. I. M. (Nepal Journal of Science and Technology, 2007)
The feasibility of in-situ bioremediation of atrazine-contaminated groundwater by Pseudomonas sp. ADP (PADP) was tested in a two-dimensional laboratory scale model aquifer. The experimental set-up consisted of three compartments: an inlet chamber, a saturated sandy aquifer with a biological permeable reactive barrier (BPRB) and an outlet chamber. Multi-layer samplers (MLSs) at 10, 25 and 40 cm from the bed base were located at 7, 28.5 (well), 42.5 (BPRB) and 55 cm from the inlet. Artificial atrazine-contaminated groundwater (1 mg/L) amended with nitrate (20 mg/L NO3- -N) flowed horizontally through the aquifer at a rate of 5.5 cm/day. Inoculation of the reactive barrier was achieved by temporarily stopping the water flow, and injecting into the reactive barrier 1 L of a PADP suspension with a concentration of 5.6 x 109 CFU/mL; water flow was resumed one hour later. To enhance bacterial activity, a citrate solution (1 g/L) was injected into the barrier twice a week. During the four months of operation, water samples were withdrawn weekly from the MLSs at each sampling station and from the inlet and the outlet, to determine the following water quality parameters: dissolved oxygen, pH, temperature, nitrate, atrazine, total dissolved solids and bacterial colony counts (CFU). The concentration of atrazine was practically unchanged from the inlet to the barrier, and an average removal of 50% was observed at the barrier. This removal in the concentration of atrazine was maintained downstream with a slight increase at the outlet, probably due to matrix heterogeneities and preferential channeling. The concentration of dissolved oxygen also decreased along the water path and the lowest value, 2.2 mg/L, was measured at the barrier and at the station downstream. A very small decline was detected in pH values, which decreased from an average of 8.4 ± 0.1 at the inlet to an average of 8.0 ± 0.1 at the outlet. The values of total dissolved solids and temperature did not change significantly throughout the aquifer. In general, low levels of nitrate reduction were detected, although up to 80% reduction was observed at the third week at location 55 cm, with no detectable decrease in the concentration of dissolved oxygen. No correlation was found between degradation of atrazine and nitrate reduction. Our results indicate that in-situ treatment may be a suitable method for the restoration of atrazine contaminated aquifers. Nepal Journal of Science and Technology Vol. 7, 2006